CONCEPTUALIZATIONS AND SCHEMATIZATIONS OF HEAD METAPHORS: A CONCEPTUAL METAPHOR THEORY - Asnita Sirait; Lia Maulia Indrayani; Rosaria Mita Amalia; Thomson Radesman Lingga (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
Human’s head takes the most important part in human’s part of body which leads to the frequent use of  head in language uses. This study therefore aims to investigate how head is conceptualized through the use of metaphor in Corpus of Contemporary American English (COCA) and how the conceptual metaphors are projected through image schemas. The data were obtained  from Corpus of Contemporary American English (COCA) as a rich data sources relevant to the study. This study applied qualitative descriptive study through the framework of the Conceptual Metaphor Theory (CMT)  proposed by Lakoff and Johnson (2008). Sentences which contain head metaphors were selected, analyzed, and categorized to relevant conceptual metaphors through the bridge of mappings to characterize the relationship between two concepts (source and target domains) in the metaphorical process and image schemas.  The findings of the study showed that head is mostly metaphorically used as a container which is conceptualized as a head is a container.The most image schemas used are containment schemas which show in-out,  full-empty,  and surface schemas. The image-schemas have indeed been shown to likely become the basis of numerous metaphorical constructions and have been helpful to understand how people cognize their world.